PENGARUH TANGIBILITY ASSET, PROFITABILITY, SIZE, BUSINESS RISK DAN GROWTH OPPORTUNITIES, TERHADAP KEBIJAKAN LEVERAGE PERUSAHAAN - Fajar Suryatama (BISECER (Business Economic Entrepreneurship), 2017)
ABSTRACTThe differences of the result research of factors which influence the policy of company leverage, push the writer to do re-research to get the current research. The research is focused on several factors which cover active structure, profitability, the company size, business risk and the company growth level in order to be known how the independent variable influence toward dependent variable.The object research is taken from the manufacture company which are listed and go public in Jakarta Stock Exchange from 2000 to 2004. The research sample is taken by using purposive sampling method with judgement type sample sampling, the sample taken fulfill the requirement and special criteria. The research takes sample from 40 companies.The research sample shows that the influences of active structure, profitability, the company size, the business risk and the company growth level toward the company leverage policy as a whole are 23% and 77% respectively the others are company leverage structure, so does the variable of the company growth level. While for the profitability variable, the company size and business risk have influences toward the company leverage policy.Keywords : Tangibility Asset, Profitability, Size, Business Risk, Growth Opportunities and Leverage.